2019
DOI: 10.1021/acs.iecr.8b05027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inorganic Salt Blending on the CO2 Separation Performance and Morphology of Pebax1657/Ionic Liquid Gel Membranes

Abstract: Gel membranes comprising inorganic salt, molten salt or ionic liquid (IL), and Pebax1657 were prepared by blending the three components in ethanol/water mixture, and their carbon dioxide separation properties were evaluated. To probe the effects of inorganic salt types and concentrations, a small amount of common inorganic salts, such as sodium chloride (NaCl), calcium chloride (CaCl2), and sodium sulfate (Na2SO4) were first doped into neat Pebax membranes. The thermal properties, surface chemistry, and gas se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…For instance, the TFC-HFM prepared by Fam et al, containing GO, showed a 42% decrease in CO 2 permeance, while the CO 2 /N 2 selectivity was preserved, after a 6-month aging period. The same authors also reported a fast physical aging in Pebax/80 wt %IL/CaCl 2 TFC-HFM, with a feed pressure of 10 bar, due to the loss of free volume in the structure of the PTMSP gutter layer . Nonetheless, there is still much work to be done in order to understand how these parameters can influence the performance of mixed-matrix ion gels.…”
Section: Perspectives and Opportunitiesmentioning
confidence: 98%
See 3 more Smart Citations
“…For instance, the TFC-HFM prepared by Fam et al, containing GO, showed a 42% decrease in CO 2 permeance, while the CO 2 /N 2 selectivity was preserved, after a 6-month aging period. The same authors also reported a fast physical aging in Pebax/80 wt %IL/CaCl 2 TFC-HFM, with a feed pressure of 10 bar, due to the loss of free volume in the structure of the PTMSP gutter layer . Nonetheless, there is still much work to be done in order to understand how these parameters can influence the performance of mixed-matrix ion gels.…”
Section: Perspectives and Opportunitiesmentioning
confidence: 98%
“…More recently, Fam et al studied the influence of different inorganic salts (NaSO 4 , NaCl and CaCl 2 ) and [C 4 mim]­[BF 4 ] IL in Pebax 1657-based membranes for CO 2 /N 2 separation. In this case, the authors used a different approach.…”
Section: Development Of Mixed-matrix Ion Gel Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ionic liquids (ILs), as a state-of-the-art kind of ambient temperature molten salt, have captured intensive insights because of their green characteristic. Close attention to the ILs has been widely paid in various aspects, such as electrolytes, energy applications, catalytic reactions, , material modifications, , and efficient gas absorbents. Compared with the traditional organic electrolytes, they are considered to be more secure because of their negligible vapor pressure, high thermal stability, and nonflammability, which have therefore been considered as a substitute for organic electrolytes in EDLCs. The cations and anions do not match in terms of size and tend to exhibit some degree of charge delocalization due to the weak interaction between the constituent ions, which is usually responsible for their high ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%